2015
DOI: 10.14421/al-mazaahib.v3i1.1378
|View full text |Cite
|
Sign up to set email alerts
|

Genealogi Gerakan Penegakan Syari’at Islam Di Indonesia

Abstract: Enforcement of Islamic law in Indonesia has historically and empirically problem. Debating in this case is not a new discourse of Islamic law, but of a "burden of history" which until this moment has not been completed. Political law of Dutch colonial that twist the facts enactment of Islamic law, caused  marginalization of the Shari'ah in the Indonesian legal system. As a result, there are fragmentation among the Muslims in the form and establishes the basic state at the beginning of independence. Two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…This finding is not in line with the view of Mahmuddin [32], which explains low understanding of the young generation among high school students about nationalism, history, and Islamism and tends to think and act radically because of the ineffectiveness of the history learning process, civic education, and religious education. This finding is also not in line with the results of Sodiqin's [14] research, which explains that the radical understanding of the younger generation is getting stronger in the form of aggressive behavior caused by a narrow and intolerant understanding of religion. The Mata Air Foundation and Alvara Research Center survey showed that 23.3% of high school students agreed with Jihad to establish an Islamic state or caliphate is not in line with the findings of this study.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This finding is not in line with the view of Mahmuddin [32], which explains low understanding of the young generation among high school students about nationalism, history, and Islamism and tends to think and act radically because of the ineffectiveness of the history learning process, civic education, and religious education. This finding is also not in line with the results of Sodiqin's [14] research, which explains that the radical understanding of the younger generation is getting stronger in the form of aggressive behavior caused by a narrow and intolerant understanding of religion. The Mata Air Foundation and Alvara Research Center survey showed that 23.3% of high school students agreed with Jihad to establish an Islamic state or caliphate is not in line with the findings of this study.…”
Section: Discussioncontrasting
confidence: 59%
“…At the beginning of the independence, there was a debate about the basis of the state. Then, Islamic nationalist groups who insisted on defending the Jakarta Charter "Belief in One Supreme God by implementing Islamic law for its adherents" finally accepted the revision of the first precepts of the Jakarta Charter [14][15][16]. This is the initial evidence of the compromise values shown by the majority group of Muslims, willing to give in for the realization of the Unitary State of the Republic of Indonesia [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jihad arbab al-dzulm wa al-bid'ah simply means jihad against tyranny and bid'ah. 42 Aligning with the issue of terrorism on a global scale makes Al-Qaeda a frightening specter. Roy (2017) stated that the radical Salafi movement or Islamic neo-fundamentalism has led to the emergence of bomb terror used to attack foreign facilities belonging to America and Europe.…”
Section: Radicalism In the Swirl Of Political Reformmentioning
confidence: 99%